Numerical modelling of ravelling in porous friction courses (PFC). Issue 3 (3rd April 2018) - Manrique-Sanchez, Laura; Caro, Silvia; Arámbula-Mercado, Edith
Abstract : Porous Friction Courses (PFCs) are asphalt mixtures located on top of pavement structures that are characterised for having high permeability properties. Although the use of PFCs provides several environmental and safety benefits, these materials typically present a short service life. This is mainly due to ravelling, a phenomenon defined as the progressive loss of aggregates from the pavement surface. This work uses a Finite Element (FE) model to investigate the potential of ravelling in PFCs. The FE model incorporates realistic geometries of PFCs that were located on top of a pavement structure and subjected to the pass of a moving wheel load. The influence of certain components of the mixture and different traffic and pavement conditions were evaluated using an energy criterion and probabilistic principles. The results suggest that ravelling is mainly a fracture Mode I process, highly influenced by the volumetric properties of the mixture and loading conditions.